Covid-19 pandemic, digital education and national development in Nigeria (2022)
The COVID-19 pandemic has wreaked havoc on the process and practice of education in nations across the globe. The pandemic however brought to fare the need oar digitalisation and utilisation of modem methods of teaching and learning in schools. Thus, the pedagogy in the System of education is affected in certain ways. This is necessary to overcome the menace and challenges the pandemic has thrown societies into. The study employed the tools of both historical and philosophical research methods to assess the relevance of digital education in the quest to promote the course of education in order to bring about national development in Nigeria. This is expected to assist Nigeria and other countries across the globe to overcome the big challenge and disruption caused by the pandemic in the practice of education. The study concluded that the place of digital education to confront the negative effects of COVID-19 pandemic in order to overcome the problems that can impede the desired growth and developments in the Nigerian society has become imperative. The paper recommends that stakeholders should brace up to embrace the realities of the 'new normal! ’ of digital education which the pandemic had brought, while individuals’ and governments' efforts should not be undermined under the guise of any form of conservatism